PENERAPAN MODEL PEMBELAJARAN NUMBER HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA VI SD NEGERI BANTARJATI 8 KOTA BOGOR PADA MATERI TAKSIRAN KELILING DAN LUAS LINGKARAN - Yusniati Yusniati (Universitas Pakuan, 2022)
THE APPLICATION OF THE NUMBER HEADS TOGETHER LEARNING MODEL TO IMPROVE THE LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS (SD NEGERI BANTARJATI 8 KOTA BOGOR ) IN THE LESSON OF ESTIMATING THE CIRCUMFERENCE AND AREA OF A CIRCLEThis study aims to find out the application of the Numbered Heads Together Cooperative learning model can improve student learning outcomes in mathematics subjects about estimating the circumference and area of a circle in class VI SD Negeri Bantarjati 8 Bogor City Semester 1 of the 2019/2020 Academic Year. Also to describe the process of improving student learning outcomes in mathematics subjects about estimating the circumference and area of a circle after using the Numbered Heads Together learning model. As well as to measure the magnitude of the increase in student learning outcomes in mathematics subjects about estimating the circumference and area of a circle after using the Numbered Heads Together Type Cooperative learning model. The results of this study indicate that using the Numbered Heads Together Cooperative learning model can be a fun variation of learning for students so that it is proven to improve student learning outcomes. Before using the Numbered Heads Together Cooperative learning model, student learning outcomes only reached an average value of 65.56 then there was an increase after using the Numbered Heads Together Cooperative learning model to 71.11 in cycle 1 and 79.31 in cycle 2. concluded that the use of the Numbered Heads Together Cooperative learning model is fun so that there is an increase in student learning outcomes. Therefore, the researcher suggests that the use of the Numbered Heads Together Cooperative learning model be socialized and used as an alternative in learning mathematics in schools within the Bogor City Education Office.Â